Mycotoxin production by Aspergillus flavus and Penicillium citrinum in competitive environment on mustard (Brassica juncea) - M.S. AHMAD (Seed Research, 2026)
Mustard (Brassica juncea L.) is an important oilseed crop of Bihar state. This state also provides ideal environment for the association of various mycotoxin producing fungal species with mustard seeds. An attempt has been made, to record the influence of microbial interactions on mycotoxin production in liquid medium by the selected toxigenic strains of Aspergillus flavus and Penicillium citrinum, respectively. Based on these results five fungal species were selected for recording their influence on mycotoxin production in the seeds of two mustard varieties viz. NDR-8501 and Raurd-101 under laboratory conditions. Maximum inhibition in aflatoxin B, (83.72%) and citrinin production (63.63%) in variety NDR-85501 was observed, when the seeds were co-cultured with Rhizopus stolonifer. In Raurd-101 variety maximum inhibition in aflatoxin B, production by A. flavus was observed with F. moniliforme (82.69%), whereas Rhizopus stolonifer inhibited citrinin production by P. citrinum (66.00%).